1954
DOI: 10.1021/jf60022a006
|View full text |Cite
|
Sign up to set email alerts
|

Antitoxidants, New Developments for Food Use

Abstract: The use of antioxidants in fats and in foods containing fats has increased greatly during the past 10 years. In addition to preventing loss from impairment of palatability, antioxidants conserve the nutritive value of foods, and thus are making an important contribution to better nutrition and to conservation of our food supply. Several substances isolated from natural sources have been found effective in increasing the keeping time of fats as measured by the active oxygen method, but none of them have the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1956
1956
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Phenolic antioxidants scavenge the peroxy radicals by hydrogen donation to produce hydroperoxides and phenoxy free radicals. Butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) are among such antioxidants and have been shown to be synergists with one another (1)(2)(3). The mechanism of the synergistic effect has not been fully disclosed.…”
mentioning
confidence: 99%
“…Phenolic antioxidants scavenge the peroxy radicals by hydrogen donation to produce hydroperoxides and phenoxy free radicals. Butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) are among such antioxidants and have been shown to be synergists with one another (1)(2)(3). The mechanism of the synergistic effect has not been fully disclosed.…”
mentioning
confidence: 99%
“…Synthetic antioxidants such as butylated hydroxyanisole (BHA) have been used as antioxidants for food since the beginning of last century [1][2][3]. It has been reported that 3-tert-butyl-4-hydroxyanisole is a much more effective antioxidant than 2-tertbutyl-4-hydroxyanisole [1].…”
Section: Introductionmentioning
confidence: 99%